INCREASED PLASMA LEVEL OF D-DIMER AS A MARKER OF HIGH ARTERIAL THROMBOSIS RISK - N. V. Furman; N. F. Puchinjan; O. M. Ansimova; P. J. Dovgalevsky (Столичная издательская компания, 2016)
Estimation of cardiovascular risk is discussed. Serum lipoproteins, glucose, fibrinogen, von Willebrand factor, tissue-type plasminogen activator, C-reactive protein etc are offered for use as laboratory indicators. At the same time new markers of high cardiovascular risk are under development. D-dimer is a product of fibrin degradation and its plasma level reflects intensity of intravascular thrombosis and fibrinolysis. Plasma level of D-dimer as a tool for estimation of cardiovascular risk and pharmacotherapy efficacy is discussed.